A Semiotic Analysis Found on Movie Poster “Shutter Island” - Ratih Utami; Eddy Setia; Deliana (LingPoet: Journal of Linguistics and Literary Research, 2021)
This research aims to know the meaning from the semiotic signs on the movie poster. The data is collected from movie poster “the shutter island” which is taken from internet site. This study used qualitative approach since the researcher focused on identifying the sign found in the movie poster of The Shutter Island. This study applied some theories of semiotics, there are theory of sign by Saussure (1974) and some other theories such as Theory of  Colour  Term by Wierzbicka (1996) which is used for identifying the meaning of colors found in the movie poster and Verbal and Visual Aspect Theory by Dyer (1986) which applied for identifying verbal sign and visual poster in this research. It can be concluded that there are two aspects which is formulated in movie poster Shutter Island, they are verbal and visual aspect. The verbal aspect includes some categories such as the masthead which exolained who is the main character in this movie, the title of the film to inform the audience about the film, where the line on the poster inform the audience the spoiled that it was the island where once people got into that island, it could be so difficult for the to get away from the island, and it shows the date the film will be released.